PENGARUH MOLASE TERHADAP AKTIVITAS KONSORSIUM BAKTERI PEREDUKSI SULFAT DALAM MEREDUKSI SULFAT (SO4-) - Punjungsari, Tyas Nyonita (Universitas Islam Balitar, 2017)
The purpose of this research is to understanding the effect of organic matter on BPS activity in reducing sulfate. Research carried out in batch culture using erlenmeyer, and using a completely randomized design (CRD). The treatment given is organic matter amounted to 308 mg / L, 617 mg / L and 1.234 mg / L and control. Each treatment was repeated 3 times. The parameters observed in this study is SO4- concentration. Using Duncan New Multiple Range Test (DNMRT) at 5% level for data analysis. The results showed that the molecular concentration of 617 mg / L was able to decrease the sulfate concentration at the fastest, then consecutively the concentration of molasses 1.234 mg / L, and control. Based on the Anova test the significant value is less than 0.05. Thus it can be stated that there is an effect of addition molasses to decrease sulfate concentration by sulfate reducing bacteria consortium.